GRAMMATICAL ERROR ANALYSIS: A STUDY ON STUDENTS’ SCIENTIFIC ABSTRACTS - Irnanda, Natasya Putri; Awalin, Arpinda Syifa (Synergy : Jurnal Ilmiah Multidisiplin, 2024)
This study examines grammatical errors in the abstracts of scientific papers of third semester students of the English language education study program, Faculty of Tarbiyah and Teacher Science, Islamic University of Sayyid Ali Rahmatullah Tulungagung. Error analysis is an established method for studying challenges in language learning. Four categories of errors, based on Corder's classification, are omission, addition, improper selection, and incorrect order of elements. Reading and note-taking techniques were used to collect data on grammatical errors made by students in their scientific work, especially abstracts which were then presented descriptively. The study shows that these errors mainly stem from limited knowledge of English grammar, interference from the students' first language, and lack of understanding or mastery of English grammar by the students. The findings emphasize the need for targeted grammar instruction to improve students' academic writing ability, especially in scientific contexts, and offer practical insights for educators in improving writing instruction.